Kauno lietuviškos knygos leidybos pradžia XIX amžiuje - Lietuvninkaitė, Nijolė (Knygotyra, 1998)
The publication of Lithuanian book in Kaunas started very late - in the middle of the 19th century. Meanwhile the history of the book in Great Lithuania already has been continuing for several centuries. This situation was determined by historical, social and economic conditions. Kaunas in the beginning of the 19th century was the very mid-province of Russian Empire where was not found any printing house, book-shop or library. When the town became the center of Kaunas government here settled 2 printing houses and has been published the official newspaper "Kovenskije gubernskije vedomosti" ("The News of Kaunas Government"). The appearance of the first Lithuanian book "Regulas ... " was initiated, issued and disseminated free of charge by the institutions of czar’s authority. In this little book there were presented instructions and advices for the state peasants about specific features of cholera, its epidemic spreading and precautionary measures and means of medical treatment under home conditions. This printing is one of means of the fight against cholera epidemic which began in 1848 in Kaunas government. The most of government people were Lithuanians, therefore czar’s authority was forced to issue the instructions in Lithuanian. This small book became the first care of public health edition in Great Lithuania. The second shortened edition appeared in 1852 when cholera epidemic has recurred. In the 19th century were printed only 9 Lithuanian printed matters. After "Regulas ... " had appeared 3 ABC books, some small printings. When the printing was prohibited 3 of them were published in Russian alphabet. The printing of Lithuanian book in Kaunas revived and started intensive way of development by getting back the Lithuanian press in the beginning of the 20th century.